2019
DOI: 10.3390/s19245415
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Simultaneous Ranging in IR-UWB Networks

Abstract: Growth in the applications of wireless devices and the need for seamless solutions to location-based services has motivated extensive research efforts to address wireless indoor localization networks. Existing works provide range-based localization using ultra-wideband technology, focusing on reducing the inaccuracy in range estimation due to clock offsets between different devices. This is generally achieved via signal message exchange between devices, which can lead to network congestion when the number of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Denote the time difference of reception of the two packets at node V ∈ {M, A, B} by P V . Then, for any nodes X ∈ {M, A, B} and Y ∈ {M, A, B}, it can be shown that [19]…”
Section: Antenna Delay Measurement System a Proposed Methodsmentioning
confidence: 99%
“…Denote the time difference of reception of the two packets at node V ∈ {M, A, B} by P V . Then, for any nodes X ∈ {M, A, B} and Y ∈ {M, A, B}, it can be shown that [19]…”
Section: Antenna Delay Measurement System a Proposed Methodsmentioning
confidence: 99%
“…In this section, we provide the comprehensive mathematical modeling, design, and implementation of the proposed system. Based on the principle of multiple simultaneous ranging (MSR) [ 34 ] and the property of time difference of reception of two packets transmitted from different sources, we formulate the proposed system to simultaneously measure the position and antenna delay values of anchor nodes in a UWB-based RTLS.…”
Section: Node Calibration Systemmentioning
confidence: 99%
“…Let denote the time difference of reception of the two sensing packets at node i . Then, for any receptor nodes i and j , it can be shown that [ 34 ] where is the TOF from node i to node j . Now, suppose that is to be computed as if it was measured by a preferred clock, and the clock of is selected as the preferred clock.…”
Section: Node Calibration Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The range between base station and the tag can be measured by the TOA algorithm. The method usually relies on the exchange of signal messages between the two nodes [18]. In order to degrade the effect of the conventional two way ranging (TWR) [19].…”
Section: Ranging Algorithmmentioning
confidence: 99%